Effects of vitamin C in enhancing the activities of antibiotics against multi-drug resistant bacteria - Yousuf, Marzia; Progya, Afia Naz (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.